Vodafone Group Plc : equity valuation - Pereira, Mário Rui Caetano Queiroga (2019)
The aim of this dissertation is to answer to two research questions: “What is the enterprise value?” and “What is the value of one share of Vodafone at the end of 2019’s fiscal year?”. In order to answer to these two questions, two different methodologies were used: the Discounted Cash-Flow (DCF) method and the Relative Valuation, supported by the P/E and EV/EBITDA multiples. Furthermore, when comparing to the stock trading on 21st September of 2018, 1.88 EUR, the valuation presents that Vodafone is undervalued in the market, since the fair value of one unit of common stock is estimated to be a ranged between 2.55 – 2.73 EUR, which should lead to a buy recommendation. This recommendation is sustained by DCF model with higher preponderance (80%) due to the fact that it was considered a more completed model to determine the final price when comparing to the Relative Valuation (20%). Nevertheless, the Relative Valuation model plays an important role as it complements the DCF model. In addition, Vodafone is also expected to acquire Liberty Global's operations in Germany, the Czech Republic, Hungary and Romania, two scenarios have been considered: Vodafone's assessment based on the contract price increase and Vodafone's assessment with a possible acquisition of Liberty Global operations. Finally it is presented a Valuation Comparison with J.P.Morgan’s Investment Research Report. Apart of being used different methodologies, both studies recommend investors to adopt a “Buy” position.